Um modelo matemático para minimização dos custos de transportes e movimentos de terra em construção de rodovias - Ubaldine, Diego torquato (2015)
This research examines the history of mathematical models that deal with resource allocation problems involving mass moving – specifically earth moving in construction of highways - which involves analysis of the evolution of models used for solving this type of problem - its applicability, advantages and disadvantages. The historical analysis of the models generates the foundation for creating a new model that includes two pertinent aspects of daily life of Brazilian companies involved in road construction: time and obstacle. Then, the new formulation is applied in a real life situation, seeking to measure its effectiveness and representativeness; for this purpose, a computational algorithm of the model is created and then used in VBA in order to facilitate the applicability of the model to both scholars of this field as to entrepreneurs and engineers who deal with the problem of mass moving in their daily professional activities.